Health economic impacts associated with the consumption of sugar-sweetened beverages in Brazil - Leal, Joice Silva Vieira; Fogal, Aline Siqueira; Meireles, Adriana Lúcia; Cardoso, Letícia de Oliveira; Machado, Ísis Eloah; Menezes, Mariana Carvalho de (Frontiers in Nutrition, 2022)
Introduction The consumption of sugar-sweetened beverages (SSBs) is among the main risk factors for non-communicable diseases (NCDs). This study aimed to estimate the financial costs of hospitalizations and procedures of high and medium complexity for NCDs attributable to the consumption of SSBs in the Brazilian Unified Health System (SUS) in 2019. Methods This ecological study used data from the Global Burden of Disease (GBD) 2019 and the Department of Informatics of the Unified Health System (DATASUS). The attributable costs were estimated from the population-attributable fraction (PAF) and the costs in the treatment of chronic diseases [type 2 diabetes mellitus and ischemic heart disease (IHD)], stratified by sex, age group, level of complexity of treatment, and federative units. Results In 2019, in Brazil, US$ 14,116,240.55 were the costs of hospitalizations and procedures of high and medium complexity in the treatment of NCDs attributable to the consumption of SSBs. These values were higher in males (US$ 8,469,265.14) and the southeast and southern regions, mainly in the state of São Paulo. However, when evaluating these results at a rate per 10,000 inhabitants, it was observed that the states of Paraná, Tocantins, and Roraima had higher costs per 10,000 inhabitants. Regarding the age groups, higher costs were observed in the older age groups. Conclusion This study revealed the high financial impact of the NCDs treatment attributed to the consumption of SSBs in Brazil and the variability among Brazilian macro-regions. The results demonstrate the urgency and need for the expansion of policies to reduce the consumption of SSBs in Brazil with strategies that consider regional particularities.